Shadow financial services and firm performance in South Africa - Sheunesu Zhou; Devi D. Tewari (Cogent Economics & Finance, 2019)
The last two decades have seen a sharp increase in shadow banking activities in both advanced and emerging economies. Shadow banks have therefore become an important part of financial markets due to their credit creation and capital allocation roles. This study investigates the impact of shadow banking on firm profitability in South Africa and evaluates the linkages between shadow banking and real economic activity. We employ single equation cointegration methods and three measures of firm profitability in our analyses; and several macroeconomic and bank specific variables are used as control variables. Our results are mixed showing that shadow banking has a negative impact on traditional banks' profitability whilst on the other hand it positively impacts non-financial firms and the overall measures of firm profitability. Our results indicate that both non-financial firms and non-bank financial institutions could be benefiting from the expansion in shadow banking activities. Targeted, functional regulation is suggested in order to promote economic activities in the shadow banking sector whilst at the same time limiting possible risks that may arise.
Keywords: C33; E44; G23; 330; shadow banking; firm profitability; cointegration; macro-economic variables